Improve the Performance of a Turbocharged Diesel Engine by Increasing the Temperature of the Exhaust Gases - Nabil Gadeer; Bahaa Baddour (Tishreen University, 2020)
In this search we present a study to improve the ability of diesel engine with turbocharger by increasing the temperature of exhaust gases. Increasing the power of the engine by injecting gas fuel into the exhaust stream covers large, non-continuous loads. Therefore, we do not have to use an engine with greater capacity to perform the same work, this means non-draining energy and environmental protection from pollution. We modeled the engine cycle, turbocharger cycle and added a combustion chamber using Matlab program, so that proposed addition showed a notable increase in torque, when ratio of diesel fuel 50% it gave an increase in torque of 24% when the speed of rotation 2000 RPM and the ratio of propane 25%, increase in torque 35% when the speed of rotation 1800 RPM at the ratio of propane 50%, and increase in torque 35% at 1800 RPM at the ratio of propane 75%. تم في هذا البحث دراسة لتحسين استطاعة محرك ديزل رباعي الأشواط مشحن عنفياً عن طريق زيادة درجة حرارة غازات العادم التي تقوم يتشغيل الشاحن العنفي. وتعمل زيادة استطاعة المحرك عن طريق حقن وقود غازي في مجرى غازات العادم على تغطية الأحمال الكبيرة غير المستمرة، بالتالي تنتفي الحاجة لمحرك ذو استطاعة أكبر لتأدية نفس العمل، وهذا يعني عدم استنزاف طاقة إضافية والحفاظ على البيئة من التلوث. قمنا في هذه الدراسة بنمذجة دارة المحرك ودارة الشاحن العنفي وأضفنا حجرة احتراق باستخدام برنامج ماتلاب وقد أظهرت الإضافة المقترحة زيادة ملحوظة في العزم، حيث أعطى البرنامج عند نسبة حقن وقود الديزل 50% نسبة زيادة في العزم 24% عند سرعة دوران 2000 RPM ونسبة وقود البروبان 25%، ونسبة زيادة في العزم 35% عند سرعة دوران1800 RPM عند نسبة وقود بروبان 50%، ونسبة زيادة في العزم 35% عند سرعة دوران 1800 RPM ونسبة وقود البروبان 75%.